Synthesis of Bis(3-indolyl)methanes Mediated by Potassium tert-Butoxide - Santos, A. Sofia (2023)
The National NMR Facility is supported by FCT, ROTEIRO/0031/2013-PINFRA/22161/2016, co-financed by FEDER through COMPETE2020, POCI, and PORLandFCT through PIDDAC) and CERMAX(022162).